Additional deleterious effects of alcohol consumption on sperm parameters and DNA integrity in diabetic mice. (10th September 2015) - Pourentezari, M.; Talebi, A. R.; Mangoli, E.; Anvari, M.; Rahimipour, M.
Summary: The aim of this study was to survey the impact of alcohol consumption on sperm parameters and DNA integrity in experimentally induced diabetic mice. A total of 32 adult male mice were divided into four groups: mice of group 1 served as control fed on basal diet, group 2 received streptozotocin (STZ) (200 mg kg −1, single dose, intraperitoneal) and basal diet, group 3 received alcohol (10 mg kg −1, water soluble) and basal diet, and group 4 received STZ and alcohol for 35 days. The cauda epididymidis of each mouse was dissected and placed in 1 ml of pre‐warm Ham's F10 culture medium for 30 min. The swim‐out spermatozoa were analysed for count, motility, morphology and viability. Sperm chromatin quality was evaluated with aniline blue, toluidine blue, acridine orange and chromomycin A3 staining. The results showed that all sperm parameters had significant differences ( P  < 0.05), also when sperm chromatin was assessed with cytochemical tests. There were significant differences ( P  < 0.001) between the groups. According to our results, alcohol and diabetes can cause abnormalities in sperm parameters and chromatin quality. In addition, alcohol consumption in diabetic mice can intensify sperm chromatin/DNA damage.